(untitled) (Fiep Bulletin - online, 2024)
Introduction: The peculiarities of evaluating student participation in Physical Education classes have proven to be a constant challenge. Registering and controlling participation variables in practical classes becomes bureaucratic and tiring considering that individually evaluating 40 to 50 students in a precise and objective way is an arduous task. Objective: The present study aimed to evaluate a digital instrument created to manage and evaluate student participation in practical classes. Methods: The study is characterized as a documentary field experience report, with data on class attendance collected and recorded in aggregate form in two 2nd year high school classes integrated into a school in the federal education network, without intervention and identification of participants, containing a total sample of 75 students, 37 male and 38 female, in regular practical classes of the discipline. A spreadsheet developed in the “Excel” software was used to record participation variables, and Student’s “t” test for independent samples was used for comparative descriptive statistical analysis. Results: When comparing the samples, there were significant differences between the two months (p<0.05), but there were no significant differences between the classes, showing an increase in student participation between the two months. Conclusion: the instrument proved to be effective in recording and quantitatively evaluating different classes and variables, and can be applied as a way of managing student participation in practical classes.